THE EFFECTS OF MINERALS ON THE CHEST CIRCUMFERENCE, BODY LENGTH AND BODY HEIGHT OF MALE BALI CATTLE - Gunawan, I Wayan; Suwiti, Ni Ketut; Sampurna, Putu (Buletin Veteriner Udayana, 2016)
This study aimed to determine the effect of adding minerals on the feed to the chest circumference, body length and height of male Bali cattle. A total of 48 of 10-12 months male bali cattle from four different places used in this study, consist of 12 male Bali cattle from each place. The chest circumference, body length and height of bali cattle were measured before treatment (base line), 1, 2 and 3 months respectively after treatment. The results showed that mineral administration in the feed was significantly increasing the chest circumference, but did not affect to body length and height of male bali cattle.
Keywords: sapi bali; mineral; lingkar dada; panjang tubuh; tinggi tubuh; bali cattle; minerals; chest circumference; body length; body height